Development of Canva-Based Interactive Learning Media for Teaching Pancasila to Elementary School Students - Muhammad Iqbal Rifai (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Pancasila education in elementary schools plays a vital role in instilling foundational national values from an early age. Despite its importance, classroom implementation frequently relies on conventional lecture methods and printed textbooks. Objective: This study aimed to develop Canva-based interactive learning media for teaching Pancasila to fourth-grade students and to evaluate its feasibility and effectiveness in improving students’ engagement and understanding. Method: The study employed a Research and Development (R&D) design using the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation phases. Data were collected through classroom observations, teacher interviews, student questionnaires, and a literature review. The participants were fourth-grade students at SD Negeri Kleco 1 Surakarta. The developed media was evaluated through feasibility testing and learning outcome assessment. Result: The feasibility assessment yielded an average score of 85%, categorised as excellent feasibility. The implementation results demonstrated an increase in students’ interest in learning and conceptual understanding after using Canva-based interactive media. These findings indicate that the developed media meet quality standards and effectively support Pancasila learning in elementary education. Conclusion: The Canva-based interactive learning media is both feasible and effective for enhancing students’ engagement and comprehension in Pancasila education. Its integration into classroom practice can support more interactive and meaningful learning experiences. Contribution: This study provides empirical evidence that digital interactive media can strengthen student participation and improve understanding of abstract civic values. It also offers a practical reference for educators seeking to integrate accessible technology into elementary school instruction.